Representaciones sociales que tienen los creyentes de una comunidad religiosa de la ciudad de Cali a cerca de la salud mental (2023)
This research arose from the premise that religious beliefs influence people’s perception and attitudes towards mental health, and as this may play a protective role in terms of suffering or presenting mental health complications, or, on the contrary, generate or intensify such complications. Therefore, it is intended to identify the social representations that members of a religious community have in Cali on mental health